Numerical investigation of multiple foils shield configuration against micro particles impact in space - Gour, Govind (2016)
This work presents a comprehensive numerical study of two foils protection shield configuration against the hypervelocity impact of micro particles in space. The smooth particle hydrodynamic technique is used in the commercial software AUTODYN 15.0. To model micro particles, three different materials were used and investigated the performance of the foils against their impact. For material modelling of foils, appreciable parameters were used to define their strength and failure. The Equation of state (shock and polynomial) was also used to see their responses under shock loading and unloading. For each projectile case a separate study was performed describing their debris cloud with geometrical and kinematic parameters. Later investigation indicated that the foils configuration was capable to reduce the damage against aluminium and floatglass while the steel projectile managed to penetrate both foils. So to restrain the steel projectile fragments a witness plate was implemented after the second foil. The shape of generated debris clouds for each projectile, were also visualized and compared their geometrical parameters. The study compares the decay of the axial velocity, kinetic energy and momentum for all three projectiles. Finally the report has been concluded by stating that the proposed two foils shield configuration was able to withstand HVI of micro particles especially when the micro particles have material properties such as aluminium and float glass while for the rigid (steel) micro particle, the shield was not capable to withstand the impact and required one witness plate with minimum thickness of lmm.